2011
DOI: 10.1149/1.3569980
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Development and Manufacturing of SOFC at Topsoe Fuel Cell A/S and Riso̸ DTU

Abstract: The SOFC development at Topsoe Fuel Cell A/S (TOFC) and Risø DTU is based on a R&D consortium which includes material development and manufacturing of materials, cells and stacks with metallic interconnects focussing on high electrochemical performance, durability and robustness. A significant effort is directed towards improvement of current generations as well as development of the next generation SOFC technology. The innovative concept of the next generation, aiming at improved reliability and robustness, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Important progress has been achieved over the last years which has led to an increase of power density, reduction of manufacturing costs, improved reliability and improved ease of integration of balance of plant (BoP) components and enabling thermal cycles (Cooper and Brandon 2017;McPhail et al 2017;Christiansen et al 2019;Li et al 2020;Shabri et al 2021). These improvements have made SOFCs an energy technology platform that offers attractive potential for electrical generation in centralised and distributed applications, resulting more competitive than MCFC.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Important progress has been achieved over the last years which has led to an increase of power density, reduction of manufacturing costs, improved reliability and improved ease of integration of balance of plant (BoP) components and enabling thermal cycles (Cooper and Brandon 2017;McPhail et al 2017;Christiansen et al 2019;Li et al 2020;Shabri et al 2021). These improvements have made SOFCs an energy technology platform that offers attractive potential for electrical generation in centralised and distributed applications, resulting more competitive than MCFC.…”
Section: Article Highlightsmentioning
confidence: 99%
“…A summary of the current state-of-the-art of industrial fuel cell technology can be found in Table . UTC/Delphi, FuelCell Energy/Versa Power Systems, NexTech Materials, and Topsoe A/S have all achieved individual voltage SOFC degradation rates of 0.5%/1000 h or better in laboratory tests. Most of these tests use either humidified H 2 or a mixture of H 2 and N 2 as their fuel source and operate in the range of 700–800 °C, with an overall push in the industry to achieve higher performance levels at lower temperatures. Two noteworthy advancements come from NexTech materials and Versa Power Systems, who have developed SOFCs with an active surface area of 800 and 1000 cm 2 , respectively.…”
Section: Commercial Activitymentioning
confidence: 99%
“…The methanol-fuelled 20 kW unit has been in operation on-board a freight vessel for over 1000 hours under actual 'field' conditions (10).…”
Section: Auxiliary Power Unitsmentioning
confidence: 99%
“…Besides laboratory testing, some of these have been in operation on a freight ship as an APU running on methanol or within a district heating scheme running on biogas. Several thousand operating hours have now been achieved (10).…”
Section: Residential Sofc Chp Unitsmentioning
confidence: 99%